The Effect of Chair Yoga on Biopsychosocial Changes in English- and Spanish-Speaking Community-Dwelling Older Adults with Lower-Extremity Osteoarthritis. Issue 7 (16th November 2016) - Park, Juyoung; Newman, David; McCaffrey, Ruth; Garrido, Jacinto J.; Riccio, Mary Lou; Liehr, Patricia
ABSTRACT: Chair yoga (CY), a mind-body therapy, is a safe nonpharmacological approach for managing osteoarthritis (OA) in older adults who cannot participate in standing exercise. However, there is no linguistically tailored CY program for those with limited English proficiency (LEP). This 2-arm randomized controlled trial compared the effects of a linguistically tailored yoga program (English and Spanish versions) on the outcomes of pain, physical function, and psychosocial factors compared to the effects of a linguistically tailored Health Education Program (HEP; English and Spanish versions). Participants with lower-extremity OA, recruited from 2 community sites, completed the Spanish ( n = 40) or English ( n = 60) version of twice-weekly 45-min CY or HEP sessions for 8 weeks. Data were collected at baseline, 4 weeks, 8 weeks, and 1- and 3-month follow-ups. English and Spanish CY groups (but neither HEP language group) showed significant decreases in pain interference. Measures of OA symptoms, balance, depression, and social activities were not significantly different between English and Spanish versions of CY and English and Spanish versions of HEP. It was concluded that the Spanish and English versions of CY and HEP were equivalent. Linguistically tailored CY could be implemented in aging-serving communities for persons with LEP.